A gradient cemented carbide tool and a method for manufacturing the same

CN122629378BActive Publication Date: 2026-10-27GANNAN LABORATORY +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611127823.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-27
Estimated Expiration
2046-07-28

AI Technical Summary

Technical Problem

η相硬度高但韧性极差,与周围基体的热膨胀系数不匹配,是微观崩刃、裂纹萌生与扩展的直接诱因,严重制约了刀具的寿命与加工稳定性

Benefits of technology

[0004]本申请旨在至少在一定程度上解决相关技术中的技术问题之一。为此,本申请的目的在于提出一种梯度硬质合金刀具及其制备方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122629378B_ABST
    Figure CN122629378B_ABST
Patent Text Reader

Abstract

The application discloses a gradient cemented carbide tool and a preparation method thereof, and belongs to the technical field of powder metallurgy. The gradient cemented carbide tool comprises a cemented carbide base, wherein the cemented carbide base comprises a core layer and a surface layer covering the core layer. Compared with the prior art, the core layer bears the high-temperature wear resistance and deformation resistance required by the tool, and the surface layer provides excellent impact resistance and buffering for the cutting edge, the mechanical properties of the two are matched, and the gradient cemented carbide tool is formed. Not only the comprehensive performance is improved, but also the surface layer material without beta phase is physically placed at the vertex of the cutting edge in advance, the path of beta phase reaching the high-activity area is completely isolated, the volume fraction of eta phase is stably lower than 1%, the root cause of the sharp corner effect is removed from the physical structure, the occurrence of micro-chipping, crack initiation and expansion is prevented, and therefore the service life and machining stability of the tool are prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of powder metallurgy technology, specifically relating to a gradient cemented carbide cutting tool and its preparation method. Background Technology

[0002] Carbide cutting tools are indispensable core tool materials in modern metal cutting. Among them, WC-Co based carbide, with tungsten carbide (WC) as the hard phase and cobalt (Co) as the binder phase, is widely used in various cutting scenarios due to its high hardness, high strength, and good wear resistance. To further improve the high-temperature wear resistance and anti-crater wear ability of the tools, the industry generally adds cubic carbide phases such as TiCN, TiC, and (Ta,Nb)C (collectively referred to as β phases) to the WC-Co matrix. The introduction of these β phases can effectively improve the red hardness of the carbide and reduce the affinity between the tool and the workpiece material, thereby significantly improving the overall performance of the tool under high-speed cutting conditions.

[0003] However, WC-Co based cemented carbide cutting tools containing the β phase have revealed a common problem recognized in the industry during long-term production practice – the "corner effect." Specifically, in the sharp corner region of the cutting edge (such as the tip arc transition zone), due to its high curvature, high surface energy, and short diffusion path caused by its geometry, this region becomes the most unstable part of the entire tool under the thermo-mechanical coupling effect of sintering cooling and subsequent cutting. The β phase is highly susceptible to selective decarburization in this region, triggering an imbalance in cobalt phase migration, ultimately generating a brittle η phase (such as Co3W3C) and an adjacent cobalt-depleted region. The η phase has high hardness but extremely poor toughness, and its thermal expansion coefficient does not match that of the surrounding matrix. It is a direct cause of micro-chipping, crack initiation and propagation, severely limiting the tool's life and machining stability. Summary of the Invention

[0004] This application aims to at least partially address one of the technical problems in the related art. Therefore, the purpose of this application is to provide a gradient cemented carbide cutting tool and a method for its preparation.

[0005] A first aspect of this application discloses a gradient carbide cutting tool. According to an embodiment of this application, the gradient carbide cutting tool includes a carbide substrate, the carbide substrate including a core layer and a surface layer covering the core layer; The core layer is composed of a first composition comprising tungsten carbide, (Ta,Nb)C solid solution, titanium carbonitride and cobalt; The surface layer is composed of a second composition comprising tungsten carbide and cobalt, but not containing a cubic carbide phase; The volume fraction of the η phase at the apex of the cutting edge sharp corner region of the gradient cemented carbide tool is less than 1%.

[0006] Compared to existing technologies, the gradient carbide cutting tools of the above embodiments of this application, through the aforementioned core layer bearing the high-temperature wear and deformation resistance required by the tool, and the aforementioned surface layer providing excellent impact buffering for the cutting edge, achieve a matching mechanical properties to form a gradient carbide cutting tool. This not only improves the overall performance, but also, by pre-placing the β-phase-free surface material at the apex of the cutting edge, completely isolates the path of the β phase to this highly active region, keeping the η phase volume fraction consistently below 1%. This eliminates the root cause of the sharp-angle effect from a physical structural perspective, preventing micro-chipping, crack initiation and propagation, thereby extending the tool's life and machining stability.

[0007] In addition, the gradient carbide cutting tools according to the above embodiments of this application may also have the following additional technical features: In some embodiments of this application, the first composition contains 6%-10% cobalt by mass, 3%-8% (Ta,Nb)C solid solution by mass, 1%-6% titanium carbonitride by mass, and the balance is tungsten carbide. And / or, in the second composition, the mass fraction of cobalt is 8%-12%, with the balance being tungsten carbide.

[0008] In some embodiments of this application, the minimum vertical distance from the vertex of the cutting edge region to the core layer boundary is not less than 20 μm.

[0009] In some embodiments of this application, the thickness of the surface layer is 15μm-25μm.

[0010] In some embodiments of this application, the radius of curvature of the blade tip region is 0.02mm-0.05mm.

[0011] In some embodiments of this application, the surface of the cemented carbide substrate is provided with a coating.

[0012] A second aspect of this application provides a method for preparing the gradient carbide cutting tool described in the first aspect. According to an embodiment of this application, the method includes the following steps: A first powder for forming the core layer and a second powder for forming the surface layer are prepared separately. The first powder is subjected to a first pressing molding to obtain a core layer preform; The second powder is spread around the core compact and then pressed to obtain the whole compact. The integral compact is sintered to obtain the gradient cemented carbide tool; The working conditions for the second pressing and forming process include: pressure of 150MPa-300MPa and holding time of 10s-30s; the working conditions for the sintering process include: sintering temperature of 1400℃-1500℃ and holding time of 30min-60min. This results in the preparation of a gradient cemented carbide tool without sharp corner effects, extending tool life and improving machining stability.

[0013] In addition, the method for preparing the gradient cemented carbide cutting tool according to the above embodiments of this application may also have the following additional technical features: In some embodiments of this application, the working conditions parameters for the first compression molding include: pressure of 100MPa-150MPa and holding time of 10s-30s.

[0014] In some embodiments of this application, the heating process of the sintering treatment includes: Increase the temperature to 580℃-620℃ at a rate of 5℃ / min-10℃ / min and hold for 60min-90min, then increase the temperature to 1400℃-1500℃ at a rate of 3℃ / min-5℃ / min and hold for 30min-60min.

[0015] In some embodiments of this application, it also includes: A coating is formed on the surface of the gradient cemented carbide cutting tool using a vapor phase deposition method.

[0016] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0017] Figure 1 This is a microscopic characterization diagram of sample A in this application.

[0018] Figure 2 This is a microscopic characterization diagram of sample D in this application.

[0019] Figure 3 This is a microscopic characterization diagram of sample E in this application.

[0020] Figure 4 This is a microscopic characterization diagram of sample F in this application.

[0021] Figure 5 This is a microscopic characterization diagram of sample G in this application.

[0022] Explanation of reference numerals in the attached figures: Figure 1 In the diagram: 001 is the coating layer, 002 is the surface layer, and 003 is the core layer. Detailed Implementation

[0023] The embodiments of this application are described in detail below by way of example, and are intended to explain this application, but should not be construed as limiting this application.

[0024] A first aspect of this application discloses a gradient carbide cutting tool. According to an embodiment of this application, the gradient carbide cutting tool includes a carbide substrate, the carbide substrate including a core layer and a surface layer covering the core layer; The core layer is composed of a first composition comprising tungsten carbide, (Ta,Nb)C solid solution, titanium carbonitride and cobalt; The surface layer is composed of a second composition comprising tungsten carbide and cobalt, but not containing a cubic carbide phase; The volume fraction of the η phase at the apex of the cutting edge sharp corner region of the gradient cemented carbide tool is less than 1%.

[0025] Compared to existing technologies, the gradient carbide cutting tools of the above embodiments of this application, through the aforementioned core layer bearing the high-temperature wear and deformation resistance required by the tool, and the aforementioned surface layer providing excellent impact buffering for the cutting edge, achieve a matching mechanical properties to form a gradient carbide cutting tool. This not only improves the overall performance, but also, by pre-placing the β-phase-free surface material at the apex of the cutting edge, completely isolates the path of the β phase to this highly active region, keeping the η phase volume fraction consistently below 1%. This eliminates the root cause of the sharp-angle effect from a physical structural perspective, preventing micro-chipping, crack initiation and propagation, thereby extending the tool's life and machining stability.

[0026] In this application, the cutting edge tip area can generally be understood as the geometric area formed by the intersection of the main cutting edge and the secondary cutting edge of the tool; wherein, the main cutting edge undertakes the main cutting work and removes most of the excess material on the workpiece; the secondary cutting edge assists in finishing the machined surface and controlling the surface roughness; the tool tip arc is the transition arc between the main and secondary cutting edges (usually rε = 0.2~2.0 mm), and the tool tip vertex is the geometric center point or theoretical intersection point of the tool tip arc.

[0027] In this application, the volume fraction of the η phase at the apex of the cutting edge sharp corner region of the gradient cemented carbide tool can be 0.8%, 0.5%, 0.3%, 0.1%, or lower; wherein, the η phase is a brittle intermetallic compound in cemented carbide, and its chemical formula is usually (W,M)6C or (W,M)3C (M is a binder metal such as Co or Ni).

[0028] In some specific embodiments of this application, the surface layer is composed of a composition containing only tungsten carbide (WC) and cobalt (Co), without any cubic carbide phase (β phase); and in any cross-sectional metallographic structure of the cutting edge tip region, the aforementioned core layer is not exposed at the outermost apex of the cutting edge. In other words, the material at the cutting edge apex is entirely formed by sintering the WC-Co composition of the surface layer. In the microstructure at this apex, the volume fraction of the brittle η phase is controlled to be below 1%, or even completely absent.

[0029] In addition, the gradient carbide cutting tools according to the above embodiments of this application may also have the following additional technical features: In some embodiments of this application, in the first composition, the mass fraction of cobalt is 6%-10% (e.g., 6%, 7%, 8%, 10%, or any range thereof), the mass fraction of (Ta,Nb)C solid solution is 3%-8% (e.g., 3%, 5%, 6%, 8%, or any range thereof), the mass fraction of titanium carbonitride is 1%-6% (e.g., 1%, 2%, 4%, 5%, 6%, or any range thereof), and the balance is tungsten carbide; and / or, in the second composition, the mass fraction of cobalt is 8%-12% (e.g., 8%, 10%, 11%, 12%, or any range thereof), and the balance is tungsten carbide. From a material composition perspective, by adopting the above ratios, the compatibility between the core layer and the surface layer is better, and it can meet most cutting scenarios. Meanwhile, in the surface layer, the mass fraction of cobalt is preferably 8%-12%, higher than that in the core layer, to provide superior edge toughness.

[0030] In some embodiments of this application, the minimum vertical distance from the vertex of the cutting edge tip region to the core layer boundary is not less than 20 μm, for example, it can be 22 μm, 24 μm, 25 μm, etc. To ensure the absolute reliability of physical isolation, the vertical distance (i.e., the effective thickness of the surface layer) from the cutting edge vertex (i.e., the outer surface of the tool) to the lower core layer boundary is not less than 20 micrometers. This distance is much greater than the limiting diffusion distance of the core layer β phase forming elements in the surface cobalt melt during sintering, thus forming a reliable physical barrier.

[0031] In some embodiments of this application, the thickness of the surface layer is 15μm-25μm, for example, it can be 15μm, 22μm, 24μm, 25μm or any of the aforementioned values.

[0032] In some embodiments of this application, the radius of curvature of the blade tip region is 0.02mm-0.05mm, for example, it can be 0.02mm, 0.04mm, 0.05mm or any of the aforementioned values.

[0033] In some embodiments of this application, the surface of the cemented carbide substrate is provided with a coating.

[0034] A second aspect of this application provides a method for preparing the gradient carbide cutting tool described in the first aspect. According to an embodiment of this application, the method includes the following steps: A first powder for forming the core layer and a second powder for forming the surface layer are prepared separately. The first powder is subjected to a first pressing molding to obtain a core layer preform; The second powder is spread around the core compact and then pressed to obtain the whole compact. The integral compact is sintered to obtain the gradient cemented carbide tool; The working conditions for the second pressing and forming process include: a pressure of 150MPa-300MPa (e.g., 150MPa, 200MPa, 300MPa, or any range thereof), and a holding time of 10s-30s (e.g., 10s, 20s, 30s, or any range thereof); the working conditions for the sintering process include: a sintering temperature of 1400℃-1500℃ (e.g., 1400℃, 1450℃, 1500℃, or any range thereof), and a holding time of 30min-60min (e.g., 30min, 45min, 60min, or any range thereof). This process yields a gradient carbide tool without sharp corner effects, extending tool life and improving machining stability.

[0035] In addition, the method for preparing the gradient cemented carbide cutting tool according to the above embodiments of this application may also have the following additional technical features: In some embodiments of this application, the working conditions parameters of the first compression molding include: pressure of 100MPa-150 MPa (e.g., 100MPa, 120MPa, 150 MPa or any of the aforementioned values), and holding time of 10s-30s (e.g., 10s, 20s, 30s or any of the aforementioned values).

[0036] In some embodiments of this application, the heating process of the sintering treatment includes: Increase the temperature to 580℃-620℃ at a rate of 5℃ / min-10℃ / min and hold for 60min-90min, then increase the temperature to 1400℃-1500℃ at a rate of 3℃ / min-5℃ / min and hold for 30min-60min.

[0037] In some embodiments of this application, the preparation method of the above-mentioned gradient carbide cutting tool includes the following steps in actual operation: The first step is powder preparation. According to the target components of the core layer and the surface layer mentioned above, the first powder (core layer material) and the second powder (surface layer material) are prepared respectively.

[0038] The second step is core layer pre-compression molding. The first powder is filled into the core area of ​​the mold, and low pressure is applied for pre-compression to obtain a core layer preform with a fixed shape.

[0039] The third step is spreading and co-pressing. The prepared second powder is evenly spread around the core layer compact, and the spreading thickness is determined based on the target surface layer thickness and subsequent pressing shrinkage rate. Then, the entire double-material co-pressing is performed, with a pressure preferably of 150-300 MPa and a holding pressure of 10-30 seconds, so that the powder particles of the core layer and the surface layer are tightly interlocked, forming a whole compact with a clear inner and outer layer interface and a firm bond.

[0040] The fourth step is controlled atmosphere sintering. The above-mentioned integral compact is sintered in the liquid phase at 1400℃~1500℃. The sintering atmosphere needs to be precisely controlled: on the one hand, the nitrogen partial pressure is controlled within the range of 50~150Pa to suppress the decomposition of TiCN in the core layer; on the other hand, by introducing hydrocarbon gases such as CH4 or C3H8, the carbon potential of the furnace gas is maintained at 0.8~1.2 times the theoretical carbon content to prevent material decarburization. Under these sintering conditions, liquid cobalt will undergo a small amount of migration driven by surface tension, further forming a dense and continuous cobalt-rich layer on the outer surface of the tool, effectively passivating the cutting edge. However, the key is that, since the surface layer itself does not contain β-phase forming elements (Ti, Ta, Nb), and the sintering time is limited, the diffusion distance of these elements in the core layer in the surface cobalt liquid is extremely short, and they are physically confined inside the core layer. Finally, the sintered body directly forms a double-layer structure tool with a "tough surface layer covering a wear-resistant core layer, and the cutting edge consisting entirely of the surface layer".

[0041] The preparation method provided in this application has a wide process window and good consistency. The structure of the final product is determined by the coating thickness and pressing process, and it is not sensitive to fluctuations in sintering parameters. It completely avoids the quality control failure caused by atmosphere fluctuations in traditional diffusion methods, and the product qualification rate can achieve a qualitative leap, fully meeting the needs of large-scale industrial production.

[0042] In some embodiments of this application, it also includes: A coating is formed on the surface of the gradient cemented carbide cutting tool using a vapor phase deposition method.

[0043] The gradient carbide cutting tools provided in this application can also have a wear-resistant hard coating (such as TiAlN, Al2O3, etc.) deposited on their surface by chemical vapor deposition (CVD) or physical vapor deposition (PVD). Since the coating process temperature is much lower than the sintering temperature, it will not change the phase structure of the matrix. Therefore, the final cutting edge tip of the tool still maintains an excellent state with no η phase or an η phase volume fraction of less than 1%.

[0044] The embodiments of this application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. In addition, unless otherwise specified, all reagents used in the following embodiments are commercially available or can be synthesized according to the methods described herein or known methods. For reaction conditions not listed, they are also readily available to those skilled in the art.

[0045] Example 1 This embodiment provides a gradient cemented carbide cutting tool and its preparation method, specifically including the following steps: (1) Preparation of powder Surface powder: WC powder with a Fisher particle size of 4μm and Co powder with a particle size of 1.2μm were mixed at a mass ratio of 90:10. 2.2wt% of paraffin forming agent was added, and the mixture was wet-milled in a ball mill for 24 hours, followed by spray drying and granulation to obtain the surface powder.

[0046] Core layer powder: Take WC powder, (Ta 0.8 ,Nb 0.2 (Ta,Nb)C solid solution powder, TiCN powder and Co powder were prepared in a mass ratio of 84:5:3:8, i.e., Co content 8wt%, (Ta,Nb)C content 5wt%, and TiCN content 3wt%. 2.2wt% paraffin molding agent was added, and the mixture was wet-milled and dried to obtain the core layer powder.

[0047] (2) Core layer preloading The core powder is filled into the mold at 60% of the conventional blade mold cavity volume and pre-pressed at 100MPa pressure for 20s to obtain a core compact with preliminary strength and uniform density.

[0048] (3) Laying and Co-pressing The surface powder is evenly spread around the core compact, filling the remaining 40% of the cavity space. Then, it is subjected to dual-material co-pressing at 200MPa pressure and held for 20 seconds. After demolding, a whole compact with a clear interface between the core layer and the surface layer and a tight bond is obtained.

[0049] (4) Controlled atmosphere sintering The integral pressed blank was placed in a vacuum sintering furnace. The temperature was increased to 600°C at 8°C / min and held for 60 minutes to remove the paraffin forming agent. Subsequently, nitrogen gas was introduced into the furnace to maintain the nitrogen partial pressure at 100 Pa, and CH4 was introduced to adjust the furnace atmosphere carbon potential to 1.0 times the theoretical carbon content. The temperature was increased to 1450°C at a rate of 4°C / min, and held at this temperature and atmosphere for 45 minutes for liquid-phase sintering. After the holding period, the furnace was switched to pure Ar gas protection and cooled to room temperature to obtain the blank blade.

[0050] (5) Blade coating The cemented carbide cutting tool is first pickled and preheated under vacuum, then placed in a CVD reaction chamber. Reaction gases such as TiCl4, CH4, N2, AlCl3, CO2 and H2S are sequentially introduced at 1020℃ and 100mbar to deposit a TiC / Ti(C,N) / TiN / Al2O3 composite coating. After deposition, the tool is cooled in the furnace and then subjected to combined sandblasting treatment to obtain the CVD coated cemented carbide cutting tool. The obtained sample is denoted as sample A.

[0051] Metallographic examination was performed on the sharp corner region of sample A obtained in this embodiment. Scanning electron microscopy (SEM) backscattered electron imaging revealed that the outermost layer of the cutting edge is a uniformly thick WC-Co structure without β phase (i.e., without cubic phases such as TiCN, (Ta,Nb)C). At the apex of the sharp corner, the thickness of this WC-Co layer (i.e., the vertical distance from the apex to the underlying β-phase core layer) is approximately 22 μm. Image analysis software was used to statistically analyze the region near the apex (50 μm × 50 μm), revealing that the volume fraction of the η phase (Co3W3C) is 0.3%. The results indicate that this embodiment successfully controlled the η phase at the sharp corner to below 1% through physical structure pre-setting, achieving the goal of eliminating the sharp corner effect.

[0052] Example 2 This embodiment is used to verify that the present invention can maintain excellent performance under fluctuating sintering atmosphere, and specifically includes the following process: (1) Preparation of powder Same as Example 1.

[0053] (2) Core layer preloading Same as Example 1.

[0054] (3) Laying and Co-pressing The difference from Example 1 is that the covering and co-pressing pressure is adjusted to 150 MPa, and the pressure is held for 30 seconds.

[0055] (4) Controlled atmosphere sintering The difference from Example 1 is that the nitrogen partial pressure was controlled at 50 Pa, the carbon potential was adjusted to 0.85 times the theoretical carbon content with C3H8, the temperature was raised to 1450℃ and held for 60 minutes, and the resulting sample was recorded as Sample B.

[0056] The test results showed that the distance from the tip of the cutting edge of sample B to the core boundary was also approximately 22 μm, and the volume fraction of the η phase at the tip was 0.5%. Compared with Example 1, although the atmosphere was at a lower carbon potential, the risk of decarburization to generate the η phase was still extremely low because there was no physical β phase at the tip of the cutting edge, indicating that the process window of the present invention is wider.

[0057] Example 3 This embodiment illustrates the adaptability of adjusting the composition of the surface layer and core layer to the structure, specifically including the following process: (1) Preparation of powder The difference from Example 1 is as follows: 1) The surface powder is prepared according to WC:Co=88:12 (Co content 12wt%).

[0058] 2) Core layer powder according to WC:(Ta 0.8 ,Nb 0.2 The formula is prepared with C:TiCN:Co = 78:7:5:10 (Co content 10wt%).

[0059] (2) Core layer preloading Same as Example 1.

[0060] (3) Laying and Co-pressing The difference from Example 1 is that the covering and co-pressing pressure is adjusted to 300 MPa, and the pressure is held for 10 seconds.

[0061] (4) Controlled atmosphere sintering The difference from Example 1 is that the nitrogen partial pressure is 150 Pa, the carbon potential is adjusted to 1.15 times the theoretical carbon content with CH4, the temperature is raised to 1450℃ and held for 30 minutes, and the resulting sample is recorded as sample C.

[0062] Tests showed that the tip of the cutting edge of sample C was approximately 35 μm from the core layer boundary, and no η phase (volume fraction less than 0.1%) was detected at the tip. A continuous cobalt-rich layer with a thickness of approximately 25 μm was formed on the outer surface of the tool, which will provide a superior impact-resistant substrate for the coating.

[0063] Comparative Example 1 This comparative example provides a method for preparing gradient cemented carbide cutting tools using the traditional atmosphere gradient method, specifically including the following steps: (1) Preparation of powder The difference from Example 1 is that a single powder with the exact same core layer composition as in Example 1 is used, i.e., no surface layer.

[0064] (2) Press molding A single powder was directly pressed into a single-layer compact under a pressure of 200 MPa and a holding pressure of 20 s.

[0065] (3) Controlled atmosphere sintering It is exactly the same as Example 1.

[0066] The sample obtained in this comparative example is designated as sample D. Metallographic analysis shows that in the sharp corner region of sample D, the β phase containing Ti, Ta, and Nb extends directly to the apex. In this high-curvature region, the residual β phase undergoes selective decarburization, resulting in the precipitation of a large amount of η phase, with a volume fraction as high as 4.5%. This comparative example demonstrates that simply controlling the atmosphere while still using a single-component structure cannot solve the problem of residual β phase at the sharp corner and the resulting η phase embrittlement.

[0067] Comparative Example 2 The only difference between this comparative example and Example 1 is that: (1) During the laying and co-pressing process, the pressure is reduced to 100MPa and held for 5 seconds.

[0068] The sample obtained in this comparative example is designated as Sample E. Testing showed that the overall compact density of Sample E was insufficient. During liquid-phase sintering, the interface between the core layer and the surface layer became blurred due to intense mass migration, and a large amount of β-phase particles from the core layer penetrated into the originally pure surface layer. Hard phases containing Ti, Ta, and Nb were detected again in the sharp-corner regions, and the volume fraction of the η-phase increased to 2.8%.

[0069] Comparative Example 3 The only difference between this comparative example and Example 1 is that: (1) The holding time at 1450℃ during controlled atmosphere sintering is shortened to 15 minutes.

[0070] The sample obtained in this comparative example is designated as sample F. Testing showed that, due to the pre-designed structure, no β phase was detected in the sharp corner region of the cutting edge of sample F, indicating that physical isolation was effective. However, due to insufficient holding time, the liquid phase Co failed to migrate sufficiently and form a continuous cobalt-rich layer of a certain thickness on the surface. The distance from the cutting edge apex to the underlying core layer in this region was only about 4 μm, far lower than the preferred 20 μm of this invention. This will result in the cutting edge lacking a sufficiently thick toughening layer for buffering when subjected to cutting impact, limiting the improvement in the coating's anti-chipping performance.

[0071] Comparative Example 4 The only difference between this comparative example and Example 1 is that: (1) The surface powder is adjusted to WC powder, (Ta 0.8 ,Nb 0.2 The solid solution powder of C and the powder of Co were prepared in a mass ratio of 84:6:10, that is, the content of Co was 10wt%, and the content of Ta was 10wt%. 0.8 ,Nb 0.2 The carbon content is 6 wt%. Similarly, 2.2 wt% paraffin molding agent is added, and the mixture is wet-milled and dried to obtain a surface powder.

[0072] The sample obtained in this comparative example is denoted as sample G. The test results show that the surface of sample G contains cubic phases of Ta and Nb, without a cobalt-rich gradient layer on the surface, and the sample exhibits a homogeneous structure.

[0073] Furthermore, the microscopic characterization diagrams of samples A, D, E, F, and G are shown in the following figures, respectively. Figure 1 , Figure 2 , Figure 3 , Figure 4 and Figure 5 As shown.

[0074] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0075] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A gradient carbide cutting tool, characterized in that, It includes a cemented carbide substrate, the cemented carbide substrate comprising a core layer and a surface layer covering the core layer; The core layer is composed of a first composition comprising tungsten carbide, (Ta,Nb)C solid solution, titanium carbonitride and cobalt; The surface layer is composed of a second composition comprising tungsten carbide and cobalt, but not containing a cubic carbide phase; The volume fraction of the η phase at the apex of the cutting edge sharp corner region of the gradient cemented carbide tool is less than 1%; The method for preparing the gradient carbide cutting tool includes the following steps: A first powder for forming the core layer and a second powder for forming the surface layer are prepared separately. The first powder is subjected to a first pressing molding to obtain a core layer preform; The second powder is spread around the core compact and then pressed to obtain the whole compact. The integral compact is sintered to obtain the gradient cemented carbide tool; The working conditions for the second pressing and molding process include: pressure of 150MPa-300MPa and holding time of 10s-30s; the working conditions for the sintering process include: sintering temperature of 1400℃-1500℃ and holding time of 30min-60min.

2. The gradient carbide cutting tool according to claim 1, characterized in that, In the first composition, the mass fraction of cobalt is 6%-10%, the mass fraction of (Ta,Nb)C solid solution is 3%-8%, the mass fraction of titanium carbonitride is 1%-6%, and the balance is tungsten carbide; And / or, in the second composition, the mass fraction of cobalt is 8%-12%, with the balance being tungsten carbide.

3. The gradient carbide cutting tool according to claim 1, characterized in that, The minimum vertical distance from the vertex of the cutting edge region to the core layer boundary is not less than 20 μm.

4. The gradient carbide cutting tool according to claim 1, characterized in that, The thickness of the surface layer is 15μm-25μm.

5. The gradient carbide cutting tool according to claim 1, characterized in that, The radius of curvature of the sharp corner region of the cutting edge is 0.02mm-0.05mm.

6. The gradient carbide cutting tool according to any one of claims 1-5, characterized in that, The surface of the cemented carbide substrate is coated.

7. The gradient carbide cutting tool according to claim 1, characterized in that, The working conditions for the first compression molding include: pressure of 100MPa-150MPa and holding time of 10s-30s.

8. The gradient carbide cutting tool according to claim 1, characterized in that, The heating process for the sintering treatment includes: Increase the temperature to 580℃-620℃ at a rate of 5℃ / min-10℃ / min and hold for 60min-90min, then increase the temperature to 1400℃-1500℃ at a rate of 3℃ / min-5℃ / min and hold for 30min-60min.

9. The gradient carbide cutting tool according to claim 1, characterized in that, Also includes: A coating is formed on the surface of the gradient cemented carbide cutting tool using a vapor phase deposition method.

Citation Information

Patent Citations

  • Coated hard alloy cutter and preparation method thereof

    CN120734334A